Odniesienia do języka ojczystego jako strategia uczenia się gramatyki języka obcego: perspektywa polskich uczniów języka angielskiego - Wach, Aleksandra (Neofilolog, 2017)
This article reports the findings of a qualitative study aimed at investigating the use of L1-based grammar learning strategies by beginnerlevel Polish learners of L2 English. The research looked into the participants’ accounts of their strategy use and into their perceptions about the usefulness of referring to one’s L1 in learning L2 grammar. Semistructured interviews were conducted as a data elicitation procedure. The findings pointed to considerable reliance on L1-based strategies, such as translation, in the participants’ learning of L2 English grammar, as well as positive opinions about their usefulness. L1-based strategies were reported to be used in explicit, analytic learning of L2 grammar, and their affective role in providing confidence to learners was also mentioned. Pedagogical implications include a need to raise learners’ awareness of the complex roles of the L1 in L2 learning and give them training in the use of specific strategies in order to make L1-based strategy use more informed.